Distribution of drug-resistant genes in alveolar lavage fluid from patients with psittacosis and traceability analysis of causative organisms - Lu, Huiqun; Yuan, Jing; Wu, Zeming; Wang, Lingwei; Wu, Shuang; Chen, Qiongcheng; Zhang, Zhen; Chen, Zhigao; Zou, Xuan; Hu, Qinghua; Feng, Tiejian; Lu, Jianhua; et al. (Frontiers in Microbiology, 2023)
Background: Chlamydia psittaci is a small bacterium often found in birds, including poultry, and domesticated mammals, which causes psittacosis (or parrot fever) in humans. Different strains of C. psittaci respond variably to antibiotics, suggesting a possible risk of antibiotic resistance. In general, different genotypes of C. psittaci have relatively stable hosts and different pathogenicity. Methods: Macrogenomic sequencing was performed using nucleic acids extracted from psittacosis patients' alveolar lavage fluid samples and analyzed for genetic variability and antibiotic resistance genes. Nucleic acid amplification sequences specific to the core coding region of the C. psittaci ompA gene were used, and a phylogenetic tree was constructed with C. psittaci genotypic sequences from other sources, including Chinese published sources. The C. psittaci found in each patient were genotyped by comparing ompA gene sequences. In addition, to better illustrate the relationship between genotype and host of C. psittaci, 60 bird fecal samples were collected from bird-selling stores for screening and C. psittaci typing. Results: Macrogenomic sequence alignment revealed the presence of resistance genes in varying abundance in samples from all three patients, including C. psittaci resistance gene sequences from two patients that matched those previously published on NCBI. Based on ompA genotyping, two patients were infected with C. psittaci genotype A and one patient was infected with genotype B. All five C. psittaci-positive samples obtained from bird-selling stores were genotype A. Both genotypes are reported to be infectious to humans. The host origin of the samples and the previously reported main sources of each genotype suggested that all but one of the C. psittaci genotype A in this study were derived from parrots, while genotype B was probably derived from chickens. Conclusion: The presence of bacterial resistance genes in psittacosis patients may affect the efficacy of clinical antibiotic therapy. Focusing on the developmental progression of bacterial resistance genes and differences in the therapeutic efficacy may facilitate effective treatment of clinical bacterial infections. Pathogenicity genotypes (e.g., genotype A and genotype B) are not limited to one animal host, suggesting that monitoring the development and changes of C. psittaci may help prevent transmission to humans.